Detailed specification of the steps of dry milling ethanol production - Kiss, Csongor (Acta Agraria Debreceniensis, 2013)
Durring the 2011 year I was given the possibilty to study in Indiana, USA for 5 months with the help of the Bloomington fellowship, and had the chance to study the bioethanol production in the given state. I focused mainly on the details of corn based dry milling large scale bioethanol production. The dry milling process is a relatively common production mode in the USA. In the coure of my research I tried to compare and to highlite the advantages of the dry milling process contrasted with the wet milling bioethanol production.